BCL6 coordinates muscle mass homeostasis with nutritional states - Hui J. Wang; Weiwei Fan; Sihao Liu; Kyeongkyu Kim; Ayami Matsushima; Satoshi Ogawa; Hyun Gyu Kang; Jonathan Zhu; Gabriela Estepa; Mingxiao He; Lillian Crossley; Christopher Liddle; et al. (Proceedings of the National Academy of Sciences, 2025)
Nutritional status is a determining factor for growth during development and homeostatic maintenance in adulthood. In the context of muscle, growth hormone (GH) coordinates growth with nutritional status; however, the detailed mechanisms remain to be fully elucidated. Here, we show that the transcriptional repressor B cell lymphoma 6 (BCL6) maintains muscle mass by sustaining GH action. Muscle-specific genetic deletion of BCL6 at either perinatal or adult stages profoundly reduces muscle mass and compromises muscle strength. Conversely, muscle-directed viral overexpression of BCL6 significantly reverses the loss of muscle mass and strength. Mechanistically, we show that BCL6 transcriptionally represses the suppressor of cytokine signaling 2 to sustain the anabolic actions of GH in muscle. Additionally, we find that GH itself transcriptionally inhibits BCL6 through the Janus kinase and signal transducer and activator of transcription 5 (JAK/STAT5) pathway. Supporting the physiologic relevance of this feedback regulation, we show the coordinated suppression of muscle Bcl6 expression with the induction of GH in the fasted state. These findings reveal the complexity of the feedback controls modulating GH signaling and identify BCL6 as a key homeostatic regulator coordinating muscle mass with nutrient availability. Moreover, these studies open avenues for targeted therapeutic strategies to combat muscle-wasting conditions.